(3GdcGajIs - (3GdeGdcj GdeUQj GdCSfhj, CHh YeQh, GHf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ, J(B646(3g`s ((3MSf Hf ejGd UGMH YeQ GdOjf SfGejs)
(3ChdgG (B:s
(3GdcdeI daX hVY deYfi eaQO hgj GSe haYd hMQa dCfgG EeG Cf JOd Ydi eYfi aj faSgG Ch dG GdKGfj GdMQas
(3BNQgG (B:s
(3hGdeNaaI JMd aj GdSGcf ajQO eG MPa hGdeaJhM eG bHdgG JbdH CdaGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 211s
(3eYLe GdeDdajf(B: 2 / 366s
(3cTa GdXfhf(B: 2 / 1370s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs